PENGARUH MANAJEMEN LABA, LIKUIDITAS, SOLVABILITAS DAN PROFITABILITAS TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN - Panjaitan, Yefta Rinaldi Yusak; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to find out the influence of earnings management, liquidity, profitability, solvability to the disclosure level of annual financial statement on the manufacturing companies which are listed in Indonesia Stock Exchange in the 2010-2013 periods. The discretionary accrual, current ratio, return on assets, and debt to equity ratio are the ratios and the formulas which are used in this research.The result of the research is expected to become a consideration for the management in improving the quality of financial statement of the company. The F test shows that discretionary accrual, current ratio, return on assets, and debt to equity ratio are feasible to be as the explanatory variables to the disclosure level of financial statement. Meanwhile, the t test shows that discretionary accrual, current ratio, and return on assets, and debt to equity ratio variables do not have any influence to the disclosure level of financial statement.Keywords: Discretionary Accrual, Current Ratio, Return On Assets, Debt to Equity Ratio, the Disclosure Level Of financial Statement.